The Final Mission : Preserving NASA's Apollo Sites - Westwood, Lisa; Donaldson, Milford Wayne; O'Leary, Beth Laura (Book collections on Project MUSE., 2017)
This book considers the archaeology of the facilities and sites on Earth that helped facilitate the Mercury, Gemini, and Apollo programs.